Research in personnel and human resources management - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben, Jonathon R. B. (Research in personnel and human resources management, 2020)
Research in Personnel and Human Resources Management serves as the premier annual series dedicated to the exploration of cutting-edge topics in the field of human resources management. This volume publishes theoretical and conceptual advancements in the field of human resources management related to leadership, the power of dyadic relationships in leadership development, ethical decision-making, prosocial advocacy for healthcare organizations, discrete incivility, mindfulness, and technological adaptations in employee selection.